Marketing Strategy Through Instagram Social Media - Izzat Rizal (International Journal of Education, Information Technology, and Others, 2023)
This study discusses social media Instagram. Social media is a coffee shop marketing strategy solution. Coffee shops are relatively more in demand by customers, especially millennials, who are also a generation that is active in social media, especially Instagram. In this study researchers used the theory of marketing strategy. This study used qualitative methods, data collection techniques used were interviews with 1 key informant and 3 informants, observation, documentation and literature study. The validity of the data carried out by researchers is through triangulation of sources. The research results from data analysis and discussion show that social media Instagram is quite successful as a marketing strategy for the image of the coffee shop @ceritacoffee.id